Correction: Chemical structure modulation in conductive MOFs by adjusting the oxidation state of the ligand and introducing alkali metal ions. Issue 31 (1st April 2022) - Wu, Xiaoyu; Wu, Haowei; Wu, Sicheng; Sun, Yimeng; Zhu, Jia; Zou, Ye; Xu, Wei; Zhu, Daoben
Abstract : Correction for 'Chemical structure modulation in conductive MOFs by adjusting the oxidation state of the ligand and introducing alkali metal ions' by Xiaoyu Wu et al., Chem. Commun., 2022, 58, 2702–2705, DOI: ; 10.1039/D1CC06407J .